Tropienie śladów "Biblii" w "Kolekcji Kryminałów" Joanny Chmielewskiej = Searching for the Traces of the "Bible" in the Collection of Joanna Chmielewska's Detective Novels - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the presence of the Bible in the language of the detective novels by JoannaChmielewska. The attention is paid to the biblical motifs (fratricide), biblical styling of the languagein the novel "All Red" and the presence of biblisms in the novels. Chmielewska uses assimilated names, for instance, manna, Gehenna, Apocalypse; phraseology present in Polish language thanks to the translation of the Bible by Jakub Wujek in the sixteenth century, for example: Sodom and Gomorrah, doomsday, Jericho trumpet, scapegoat. All these formulas have lost their religious meaning and are used to emphasize the emotions in the novels.
Keywords: Chmielewska, Joanna (1932-2013); literatura polska - 20 w. - tematyka; literatura polska - 21 w. - tematyka; powieść kryminalna; biblizmy